Pengaruh Servant Leadership terhadap Kinerja Individu di Mediasi Psikologi Empowerment - Sherly Amalia Fernanda; Wahyu Eko Pujianto (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
The aim of this research is to determine the influence of servant leadership on individual performance in the psychological mediation of empowerment. This research uses a quantitative approach with the employee population of PT Trikayarasa Jaya Food in Sidoarjo. The sample used was 70 employees of PT Trikayarasa Jaya Food. Data collection was carried out through questionnaires. The analysis in this research uses Partial Least Square (PLS) with SmartPLS 4.0 software. There are two model specifications used in PLS, namely: outer and inner models. The results of this research found that servant leadership influences individual performance, servant leadership influences the psychology of empowerment, individual performance influences the psychology of empowerment, psychology of empowerment mediates servant leadership on individual performance.